In vivo time-lapse fluorescence imaging of individual retinal ganglion cells in mice - Walsh, Mark K. (2007)
We have developed a technique that permits time-lapse imaging of retinal ganglion cells (RGCs), their dendritic arbors and their axons in mammals in vivo. This technique utilizes a standard confocal laser scanning microscope, transgenic mice that express yellow fluorescent protein (YFP) in a subset of RGCs and survival anesthesia techniques. The same individual RGCs with their dendritic arbors and axons were multiply imaged in vivo in both adult and juvenile mice. Additionally, the same RGC that was imaged in vivo could then be located and imaged in fixed retinal whole mount preparations. This novel technique has many potential applications.